2018
DOI: 10.1177/0046958018812972
|View full text |Cite
|
Sign up to set email alerts
|

The Technical Efficiency of Community Health Service Centers in Wuhan, China: Estimation and Policy Implications

Abstract: This study seeks to measure the technical efficiency of Community Health Service Centers (CHSCs) in Wuhan City, China, to propose some policy recommendations to improve the efficiency of CHSCs. A total of 46 CHSCs in Wuhan City were included in the study as research subjects. Data of 11 selected input and output indicators were collected from Hubei Provincial Health and Family Planning Commission. R3.2.1 statistical software was used to estimate the efficiency scores of CHSCs using Bootstrap-Data Envelopment A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…High productivity and e ciency of the TCM hospitals is highly related to the rational use of health resources (14). The rational use of health resources can be up to the well-structured health professionals (17). Even though this study showed that the number of health professionals was increasing yearly, it could not infer whether the structure of the health professionals was appropriate, especially the ratio between the western clinical doctors/pharmacists and the TCM doctors/pharmacists.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…High productivity and e ciency of the TCM hospitals is highly related to the rational use of health resources (14). The rational use of health resources can be up to the well-structured health professionals (17). Even though this study showed that the number of health professionals was increasing yearly, it could not infer whether the structure of the health professionals was appropriate, especially the ratio between the western clinical doctors/pharmacists and the TCM doctors/pharmacists.…”
Section: Discussionmentioning
confidence: 75%
“…According to a systematic review on the relative e ciency research of Chinese hospitals with DEA models conducted by Dong & Li (9), they have suggested that the technical e ciency and allocative e ciency were always misunderstood by misuse of combination of monetary and volume indicators. The review and a previous study published by our research team (17) also have mentioned that price information of the indicators is much more di cult than the volume information to be accessed in Chinese hospitals. Therefore, based on the frequency of input and output indicators used most in current studies and the feasibility of data, in this study, the input indicators were the number of health professionals and the number of actual open beds, while the number of outpatients and inpatients and the number of discharged patients were selected as the output indicators.…”
Section: Input and Output Indicators Selectionmentioning
confidence: 94%
See 2 more Smart Citations
“…In recent years, efficiency of public hospitals has become a concern for policymakers and researchers dealing with health expenditure growth in both developed and developing countries [ 1 , 2 , 3 , 4 , 5 , 6 ]. In China, this issue has long drawn scholars’ attention, and several articles have been published [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Generally, Chinese public hospitals are classified according to three standards, namely service capacity (i.e., primary, secondary, and tertiary hospitals), service items (i.e., general and specialized hospitals), and administrative subordination by government agencies in accordance with regulations.…”
Section: Introductionmentioning
confidence: 99%